Canada Council’s Killam Research Fellowships: Distribution of Awards 1968-84 - Chadwick-Jones, John K.; Carceller, A.; Vaisey, Douglas (Canadian Journal of Higher Education, 1987)
An analysis of the distribution of Killam Research Fellowships awarded by Canada Council over a seventeen-year period reveals a pattern which is examined in relation to the distribution of applications from universities. The existing situation is discussed with reference to previous studies of peer review systems and to implications for Canadian research. Encouragement of increased participation across Canada is suggested as one possible concern for Canada Council policy.